1983
DOI: 10.1080/00039896.1983.10545821
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in the Urinary Excretion of Metals and Organic Substances in “Healthy” Men

Abstract: Circadian rhythms in the urinary excretion of metals and organic substances were examined in ten "healthy" men under conditions of water loading and restriction. Four characteristic rhythms were observed: (1) decreased excretion during the night for lead and urinary flow rate; (2) decreased excretion of hippuric acid, delta-aminolevulinic acid, coproporphyrin, creatinine, and total urinary solutes during the night and morning hours; (3) increased excretion of mercury and zinc during the morning hours; and (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…However, when the two groups were combined in the analysis, the urinary excretion of Zn was significantly higher during morning hours than during each of other three time periods (p<0.05). The increase in urinary Zn excretion during morning hours has been found by Bhattacharya 5) and by us 8,9) . Pb, Cd and Cu in plasma decreased during the night hours, resembling their urinary rhythms; the rhythm of Hg in erythrocytes was similar to its urinary rhythm, showing the lowest level in the afternoon (Figs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, when the two groups were combined in the analysis, the urinary excretion of Zn was significantly higher during morning hours than during each of other three time periods (p<0.05). The increase in urinary Zn excretion during morning hours has been found by Bhattacharya 5) and by us 8,9) . Pb, Cd and Cu in plasma decreased during the night hours, resembling their urinary rhythms; the rhythm of Hg in erythrocytes was similar to its urinary rhythm, showing the lowest level in the afternoon (Figs.…”
Section: Discussionmentioning
confidence: 74%
“…variations observed within a day, in human subjects have been elucidated by many workers [1][2][3][4][5][6][7][8][9][10] . On the other hand, the rhythms of these heavy metals in blood (plasma and erythrocytes) have been reported only for Zn and Cu 2,6,[11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were collected just before the electrophysiological studies and the start of the 24-hour urine collection. The activity of the intraerythrocytic enzyme delta-aminolevulinic acid dehydratase (ALAD), the concentrations of deltaaminolevulinic acid and coproporphyrin in urine (UALA and UCP), and the blood hemoglobin and packed red blood cell volume (Hb and Hct) were measured by the methods described previously [Araki et al, 1983. BPb, MPb, PZn, MZn, PCu, MCu, the concentra tion of lead in plasma (PPb), the concentrations of zinc and copper in erythrocytes (EZn and ECu), and the amount of each metal spontaneously excreted in urine (UPb, UZn and UCu) were measured by atomic absorption spectrophotometry (Hitachi Polarized Zeeman Atomic Absorption Spectrophotometer 180-80), by the same meth ods as described in our previous reports Araki et al, 1984].…”
Section: Electre-physiologie Studiesmentioning
confidence: 99%
“…Glomerular filtration has been reported to exert an important influence on lead rhythmicity in man. The results of profile analyses suggested that the circadian rhythm of Pb in urine was affected by its plasma and erythrocyte rhythms (Araki et al 1983).…”
Section: Discussionmentioning
confidence: 99%